THE CORAL REEF CONDITION IN BERALAS PASIR ISLAND WATERS OF GUNUNG KIJANG REGENCY BINTAN KEPULAUAN RIAU PROVINCE - Fajar Sidik; Afrizal Tanjung; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study has been done on the reefs in the coastal waters of Beralas PasirIsland. It was carried out on May 2013 by deploying LIT method. The aim of thisstudy is to find out the condition of the reefs based on the percentage of HardLiving Coral Cover (HLCC) in the area. For that instance, three stations asrepresentatives were chosen purposively. As a result, the type of reefs in the areaunder study was fringing reef with different condition on each station. The station1 and 2 showed good condition with more than 50 % of HLCC coverage. Yet, itwas in moderate condition for the third station; it was about 29.10 %. There wasno dominant life’s form that found in term of both dominancy index and diversity.Keywords : Beralas Pasir Island, Coral Reef, Condition